(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study analyzed the causes and effects of poor sanitation and hygiene in secondary schools in Aba metropolis, Abia State, Nigeria. Descriptive research survey design was adopted for the study. There are 7 Local government areas in Aba metropolis in which 120 respondents were randomly selected through purposive random sampling technique guided by research advisor 2006. Three research questions guided the study. Mean scores were used as statistical tools for the study. Findings showed that the respondents agreed to the main causes, and the effects of poor sanitation in secondary schools with a grand mean of scores of 2.88, 3.08 and which is greater than the critical mean score of 2.50. It was recommended that the government and non-governmental organizations should make adequate provision of toilets and urinary facilities for the schools.